Singlebeam water column raw data (EK80 entire dataset) of RV METEOR during cruise M143 - Peter Urban; Michael Riedel; Iason-Zois Gazis; Mareike Keller; Florian Gausepohl; Line Hähnel; Jens Greinert (PANGAEA, 2025)
This dataset contains Singlebeam Echosounder (SBES) measurements acquired during the RV METEOR cruise M143 in the Black Sea between 13 and 14 December 2017. It comprises three surveys: two in water depths of 300–800 m and one on the continental shelf at approximately 120 m depth. The SBES data were collected alongside EM710 and EM122 multibeam echosounder water column imagery to support the quantification of gas emissions. No ping synchronization was applied; however, interference between the systems was minimal and considered noncritical.